2015
DOI: 10.1016/j.meegid.2015.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus infective endocarditis versus bacteremia strains: Subtle genetic differences at stake

Abstract: Infective endocarditis (IE)((1)) is a severe condition complicating 10-25% of Staphylococcus aureus bacteremia. Although host-related IE risk factors have been identified, the involvement of bacterial features in IE complication is still unclear. We characterized strictly defined IE and bacteremia isolates and searched for discriminant features. S. aureus isolates causing community-acquired, definite native-valve IE (n=72) and bacteremia (n=54) were collected prospectively as part of a French multicenter cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 38 publications
9
44
0
Order By: Relevance
“…This agrees with previous studies that also reported significant attenuation of virulence for CC30 in both the G. mellonella and murine sepsis models (Sharma-Kuinkel et al, 2015). Remarkably, our results indicate high virulence for strains of CC15, with substantial larvae mortality in the first 48 h. Although it has been associated with increased severity of infection and infective endocarditis, there is limited information about the pathogenic mechanisms of CC15 and its involvement in endovascular complications (Fowler et al, 2007; Bouchiat et al, 2015). In agreement with previous reports, we found that strains with a functional agr , associated with an up-regulated production of toxins and secreted virulence factors, were significantly more virulent than strains with a dysfunctional agr regulator (Peleg et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This agrees with previous studies that also reported significant attenuation of virulence for CC30 in both the G. mellonella and murine sepsis models (Sharma-Kuinkel et al, 2015). Remarkably, our results indicate high virulence for strains of CC15, with substantial larvae mortality in the first 48 h. Although it has been associated with increased severity of infection and infective endocarditis, there is limited information about the pathogenic mechanisms of CC15 and its involvement in endovascular complications (Fowler et al, 2007; Bouchiat et al, 2015). In agreement with previous reports, we found that strains with a functional agr , associated with an up-regulated production of toxins and secreted virulence factors, were significantly more virulent than strains with a dysfunctional agr regulator (Peleg et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, previous reports seem to indicate that no single virulence factor alone is sufficient to describe S. aureus endovascular pathogenesis and a cumulative effect from different factors probably offers the most realistic scenario (Peacock et al, 2002; Bouchiat et al, 2015). S. aureus has a highly clonal population structure with CCs comprising closely related, although not identical, genetic backgrounds (Lindsay et al, 2006; Dayan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on, but not restricted to, findings of necrosis, dissolved or deliquescent soft tissue, and fascial and muscular affection (22). The invasive non-NSTI SA control strains consisted in Bloodstream infection (BSI) strains (12 infective endocarditis, 9 bacteremia without infective endocarditis) collected during a prospective cohort study on S. aureus bacteremia (VIRSTA) (23). Those strains were chosen in order to genotypically match NSTI strains on the basis of micro-array-deduced clonal complexes (23) confirmed by whole genome sequencing (Illumina MiSeq technology, Illumina, San Diego, USA, with 16-266 x coverage, median 137).…”
Section: Methodsmentioning
confidence: 99%
“…Together these data suggest that NorK belongs to the same family as the Nor proteins previously described. To assess if this pump was widely distributed among S. aureus , BLAST analysis on a large collection of genotypically diverse bacteremia isolates (9) was performed. The results showed that 98% (123/126) harbor norK genes (identity and coverage >90%).…”
Section: Identification Of a New Putative Efflux Pumpmentioning
confidence: 99%